Antecedents and Consequences of Creativity in Teams: When and How Leader Humility Promotes Performance via Team Creativity. (25th April 2019) - Wang, Xing; Li, Hongli; Yin, Hongbiao
Abstract: The antecedents of team creativity and their effects on team task performance are explored in this study, with a particular focus on how leader humility promotes team creativity and when team creativity can be converted into performance. Hypotheses were tested via a multiple‐source and time‐lagged study with 341 employees and 104 teams from five different organizations in China. The results showed that leader humility promotes team creativity through team creative efficacy, and leader conscientiousness moderates this indirect effect. Furthermore, team creativity is more positively related to team task performance when teams are more future oriented. The theoretical contributions and management significance of these findings are discussed, followed by a discussion of limitations and directions for future research.